تحديد الضروف لاستخلاص بنزوات الصوديوم المستخدم كمضافات للاغذية وتقدير نسبه في بعض المشروبات المحلية - فرعون, بسام (University of Thi-Qar Journal of Science, 2010)
In this research it has been determined the optimum conditions for extraction of benzoate (sodium benzoate) that used as food additives and beverages.In extraction process two organic solvents used (hexane and ether) and used (HCl, HNO ) as acidic media with molar concentrations (0.1, 0.2, 0.5, 0.6, 0.7, 1 and 1.5 molar) respectively. The optimum acidic conc. determined for each solvent and the distribution ratio (D) and extraction percent (E %) also determined. The optimum acidic media for extraction with Hexane by using 0.5M HCl while for extraction with ether by using 1M HNO3. The temperature fixed at 25C The percent of benzoate estimated in some type of beverage and was found to be in the limited international level (5mg/1kg).